2016
DOI: 10.1590/0100-67622016000400001
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Aspects Related to Ligneous Vegetation in the Permanent Preservation Areas of Mineiros, Goiás, in Light of the New Native Vegetation Protection Policy - Law 12.651/2012

Abstract: -Permanent preservation areas (PPAs) adjacent to drainage channels may include forests, savannahs, or grassland Under a former environmental legislation ("Forest Code"), it was required to maintain a strip of native vegetation (at least 30 m wide) at the margin of any drainage channel, to support environmental functions. Under the current native vegetation protection policy, if a riparian margin was degraded prior to 2008, the landholder is required to regenerate a strip of only 5-20 m, in some cases. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…The application of these types of projects allows for several long-term benefits, such as economic development, job creation, degraded areas restoration and adaptation to climate change. According to Ellison et al (2017) and Siqueira et al (2016), the guarantee of ecosystem services through PSA actions enables the conservation of fauna and flora genetic flow and guarantees the preservation of water bodies PPA, contributing to the water springs do not undergo erosion processes.…”
Section: Discussionmentioning
confidence: 99%
“…The application of these types of projects allows for several long-term benefits, such as economic development, job creation, degraded areas restoration and adaptation to climate change. According to Ellison et al (2017) and Siqueira et al (2016), the guarantee of ecosystem services through PSA actions enables the conservation of fauna and flora genetic flow and guarantees the preservation of water bodies PPA, contributing to the water springs do not undergo erosion processes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lack of environmental awareness on the part of rural landowners is also preoccupying, given that the existing legislation (federal law 12,651/2012 -the Native Vegetation Protection Law) does not obligate landowners to recuperate native vegetation in plots within the APPs that are considered to have been consolidated as part of their rural property (Brasil 2012). In this context, empirical field data have shown that the plant species composition and richness of these consolidated areas may be significantly different from those of undisturbed APPs (Siqueira et al 2016).…”
Section: An Acad Brasmentioning
confidence: 99%
“…FONTE: Elaborado pelo autor ju (PA), onde observaram 9.202,21 ha de passivo ambiental em APPs, entretanto, destes, somente 3.617,21 ha estão sujeitas à recomposição, ou seja, haverá uma perda de 60,69% da área total de APPs nessas propriedades, que legalmente deixarão de ser restauradas com a aplicação do novo código florestal, uma vez que muitos usos existentes são considerados consolidados. Nesta perspectiva, Siqueira et al (2016), ao estudarem os aspectos ecológicos da vegetação lenhosa em áreas de preservação permanente, observaram que a presença de áreas consolidadas podem trazer alterações na estrutura e funcionamento das APPs existentes no Brasil com perdas significativas de espécies e indivíduos, fazendo com que estas áreas deixem de cumprir as funções ambientais previstas na legislação.…”
Section: Conflitos De Uso Nas áReas De Preservação Permanenteunclassified